Financial performance analysis of “Vision Apparels Ltd” and studying the impact of COVID-19 on the company’s financial performance - Islam, Shohana Naz (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.